Stochastic Frontier Approach for Measuring the Efficiency of Indonesian Insurance Industry - Mujadiddah, Sofina (SMART Insight, 2021)
This study uses case studies of 79 general insurance companies both conventional and sharia in Indonesia with a period of 2016-2018. The data used is secondary data obtained from the financial statements of each insurance company. This study uses a cost frontier approach and is measured based on the total cost variable (Y), total assets, equity, total claims, total premiums, total investment, and investment assets owned. From this research, it is found that the factors that influence the efficiency of sharia insurance companies are the number of claims and the amount of premiums. While the amount of insurance, the cost is influenced by claims, the amount of premiums, total assets, and the amount of investment.